2022
DOI: 10.1093/pnasnexus/pgac110
|View full text |Cite|
|
Sign up to set email alerts
|

Radical flanks of social movements can increase support for moderate factions

Abstract: Social movements are critical agents of social change, but are rarely monolithic. Instead, movements are often made up of distinct factions with unique agendas and tactics, and there is little scientific consensus on when these factions may complement – or impede – one another's influence. One central debate concerns whether radical flanks within a movement increase support for more moderate factions within the same movement by making the moderate faction seem more reasonable– or reduce support for moderate fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…There was no evidence for a population-level backlash in attitudes to environmental problems in response to the rebellion (Kountouris & Williams, in press;Smith, 2019). This is also generally consistent with further recent experimental evidence suggesting that disruptive protest does not necessarily reduce support for mainstream environmental issues, even amongst demographics typically hostile to such protest (Bugden, 2020;Simpson et al, 2022).…”
Section: Attitudes To Environmental Problems: Concern and Dissatisfac...supporting
confidence: 89%
See 4 more Smart Citations
“…There was no evidence for a population-level backlash in attitudes to environmental problems in response to the rebellion (Kountouris & Williams, in press;Smith, 2019). This is also generally consistent with further recent experimental evidence suggesting that disruptive protest does not necessarily reduce support for mainstream environmental issues, even amongst demographics typically hostile to such protest (Bugden, 2020;Simpson et al, 2022).…”
Section: Attitudes To Environmental Problems: Concern and Dissatisfac...supporting
confidence: 89%
“…Extreme protest can therefore be seen as unjustified when it appears to ignore legitimate routes to change, but when legitimate routes are perceived as inadequate, extreme protest may not damage the broader movement. Experimental work has demonstrated that a radical flank effect can apply to the climate movement, whereby support for the movement mainstream can be increased by exposure to a faction using unpopular disruptive tactics, because the mainstream looks better in comparison (Simpson et al, 2022). The above reviewed literature focuses on radical environmental protest, but we note that similar positive and negative effects have been found regarding radical tactics deployed for other causes such as civil rights (Shuman et al, 2021).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations